A rare case of PLA2R- and THSD7A-positive idiopathic membranous nephropathy - Wanderley,David Campos (2020)
ABSTRACT Idiopathic membranous nephropathy (IMN) is a frequent cause of nephrotic syndrome in adults. In terms of etiology, the condition may be categorized as primary/idiopathic or secondary. Literature on the pathophysiology of IMN has indicated the presence of autoantibodies (PLA2R and THSD7A) directed against podocyte antigens. The detection of antibodies against a domain favors IMN. The presence of autoantibodies against one of the domains would in theory exclude the possibility of there being autoantibodies against the other domain. However, cases of patients with PLA2R- and THSD7A-positive disease have been recently reported, showing that antibodies against two targets may be concomitantly produced via yet unknown pathophysiological mechanisms. This study reports the case of a 46-year-old male patient with nephrotic-range proteinuria, hematuria, hypoalbuminemia, and hypercholesterolemia submitted to biopsy and histopathology examination (LM, IF, IHC, and EM) eventually diagnosed with PLA2R- and THSD7A-positive IMN associated with IgA nephropathy, stressing our experience with the use of IgG subclasses, PLA2R, and THSD7A in the workup for MN and the relevance of adopting a broad and adequate approach to elucidating and acquiring knowledge of the pathophysiology of IMN.